2021
DOI: 10.1039/d0qm01009j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of kidney disease biomarkers based on fluorescence technology

Abstract: This review summarizes the recent progress in the development of fluorescent probes and methods for the detection of biomarkers for the diagnosis of kidney diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 124 publications
0
22
0
Order By: Relevance
“…GST can be used as a biomarker for early cancer detection and/or diagnosis. It has been reported that excessive GST in blood and urine specimens is associated with the occurrence of kidney and liver diseases, and the highest expression is in extrahepatic tissues. , Hence, the analysis of GST in genuine samples such as blood and urine is essential and desirable.…”
Section: Results and Discussionmentioning
confidence: 99%
“…GST can be used as a biomarker for early cancer detection and/or diagnosis. It has been reported that excessive GST in blood and urine specimens is associated with the occurrence of kidney and liver diseases, and the highest expression is in extrahepatic tissues. , Hence, the analysis of GST in genuine samples such as blood and urine is essential and desirable.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Here we have applied sequestration to improve the sensitivity of one biosensor and two bioassays all targeting the protein neutrophil gelatinase-associated lipocalin 52,53 (NGAL): an EAB sensor, a paper-based dipstick assay, and an ELISA. Plasma and urine NGAL levels above various threshold values are indicative of acute kidney damage [54][55][56] , with the relevant reported cut-offs in urine of 2 nM for patients with IgA nephropathy 57 , 5 nM for patients with chronic heart failure 56 , 6 nM infants after cardiac surgery 55 , and 85 nM for acute kidney damage (AKI) in adults 58 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…However, the techniques often required prelabeled molecular beacons or peptides, which can be time consuming, costly, and difficult to synthesize . To address this deficiency, researchers have developed several self-assembling methodologies by integrating different substrates with signal enhancing reported through noncovalent interactions, including a series of aggregation induced emission luminogens (AIEgens). , These strategies generally offer the additional advantages of a broad concentration range and a high signal-to-noise ratio. However, these fluorescence-based methods rely on noncovalent interactions that can be affected by reaction medium, ionic strength, surface morphology, and protein foldedness so may introduce large variation among experiments and thus have a relatively low reliability. , Surprisingly, the use of covalent probes for the in situ formation of a sensing system for the detection of trypsin activity has not been reported.…”
Section: Introductionmentioning
confidence: 99%